The impact of social media communication on personal brand management - Machado, Evelin (2022)
In contemporary societies, forms of communication have become, in many ways, predominantly online. The rise of social media has reshaped the culture of communication and created new virtual environments offering multiple opportunities for individuals to create profiles on different platforms, to communicate both personally and professionally. Although there is research on the phenomenon of Branding in social media, it is observed that the people-related perspective presents gaps in conceptual alignment and scientific depth and therefore holds immense room for progression. Thus, the objective of this article is, through a theoretical revision, to investigate and discuss the influence of communication practices and dynamics in the process of Personal Brand Management in social media, in order to contribute to overcome some of the gaps in scientific knowledge and enable the use of this knowledge by society in general.